The Effectiveness of Animal Anatomy Practice in Biology Education FKIP UMS at 2011/2012 and 2012/2013 Based on the Final Result of Practice - Endang Setyaningsih; Shinta Dwi Kurnia; Dwi Purbowati (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
The Application of new regulations in the UMS is 2 SKS likes 100 minutes imposed on schedule online cause practical implementation in the education department of biology FKIP UMS academic year (TA) 2012/2013 unchanged unlike the previous year. This resulted in the practicuml implementation of the system changes from the planning, organizing, implementing, monitoring, and evaluation of learning lab system that can affect to the student learning outcomes. The purpose of this study was to determine the effectiveness of the implementation of the Animal Anatomy lab in biology laboratories of the academic year 2011/2012 and 2012/2013 based on the end of the value of the final practicum. This type of research is descriptive quantitative test effectiveness ratio to determine how much percentage rate target is achieved above the target set in the practicum implementation Anatomy Animals (AH) at TA 2011/2012 and TA 2012/2013 and Mann-Whitney test (non-parametric ) to determine differences in effectiveness between the implementation of AH practical at TA 2011/2012 and 2012/2013 in terms of the value of the final practicum. Sources of data in this study were obtained through the techniques of documentation by gathering data on their respective academic year. The results of the test showed that the ratio of the effectiveness ratio was 122.34% in TA 2011/2012 and the effectiveness ratio was 145.56% in TA 2012/2013. An activity is said to be effective if  the ratio of the effectiveness is reaches above one hundred percent. The results of Mann-Whitney test showed that the probability value is 0.000 <0.05, then H0 is rejected it means that there is no significancy differences in the effectiveness between of implementation AH practicum in biology lab UMS in academic year 2011/2012 and 2012/2013 based on of the value of the final practicum, It can be concluded that, the implementation AH practical in biology lab FKIP UMS at TA 2011/2012 and 2012/2013 have been effective, but there are significant differences in the effectiveness between the implementation AH practicum at TA 2011/2012 and 2012/2013 based on the value of the final practicum.Keywords: learning management, animal anatomy, effectiveness, effectiveness ratio